2020
DOI: 10.48550/arxiv.2003.03928
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effective potential approach to hybrid synchronization transitions

Je Ung Song,
Jaegon Um,
Jinha Park
et al.

Abstract: The Kuramoto model exhibits different types of synchronization transitions depending on the type of natural frequency distribution. To obtain these results, the Kuramoto self-consistency equation (SCE) approach has been used successfully. However, this approach affords only limited understanding of more detailed properties such as the stability and finite size effect. Here, we extend the SCE approach by introducing an effective potential, that is, an integral version of the SCE. We examine the landscape of thi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A hybrid phase transition is a discontinuous transition but with criticality. Such a transition occurs in several a) Electronic mail: bkahng@snu.ac.kr complex systems, including cascade failure of interdependent networks 5 , k-core [6][7][8] , cooperative epidemic spreading [9][10][11][12] and synchronization [13][14][15][16][17] . However, a possible hysteresis together with critical behavior in hybrid phase transitions has been rarely reported thus far, even though hysteresis in discontinuous transitions was investigated in explosive synchronization [18][19][20] and percolation [21][22][23][24][25][26][27][28][29] in complex systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A hybrid phase transition is a discontinuous transition but with criticality. Such a transition occurs in several a) Electronic mail: bkahng@snu.ac.kr complex systems, including cascade failure of interdependent networks 5 , k-core [6][7][8] , cooperative epidemic spreading [9][10][11][12] and synchronization [13][14][15][16][17] . However, a possible hysteresis together with critical behavior in hybrid phase transitions has been rarely reported thus far, even though hysteresis in discontinuous transitions was investigated in explosive synchronization [18][19][20] and percolation [21][22][23][24][25][26][27][28][29] in complex systems.…”
mentioning
confidence: 99%
“…Thus, the transition is hybrid. A recent study showed that an ad-hoc potential 17 , proposed analogously to the Landau free energy, exhibits a flat landscape as it appears in colloidal metamagnetic systems 3,4 . The order parameter is uniquely determined except at the critical point.…”
mentioning
confidence: 99%